Desain dan Analisa Pengaruh Jumlah Mata Pisau Serta Ukuran Mesh terhadap Kapasitas Bubuk Cabai yang dihasilkan pada Mesin Penepung Cabai Tipe Disk Mill Ffc 15 - Haidar Alia Fika Rahma; Ach. Muhib Zainuri (Pusat riset dan Inovasi Nasional, 2026)
Post-harvest handling of chili in Indonesia is still largely done manually, requiring a relatively long processing time and producing products with a non-uniform level of fineness. This condition impacts low production efficiency and the quality of processed chili. Therefore, the application of appropriate technology in the form of a chili flour machine is needed to increase production capacity and consistency. This study aims to analyze the effect of the number of blades and mesh size on the production capacity of a disk mill type FFC 15 chili flour machine. The research method used was an experiment with a factorial design, involving two variations in the number of blades, namely three and four blades, and three variations in mesh size, namely 0.5 mm, 1 mm, and 3 mm. Each treatment combination was carried out three times. The results showed that the number of blades and mesh size had a significant effect on the machine's production capacity. The best treatment combination was obtained by using four blades with a mesh size of 3 mm, which resulted in a production capacity of 6.84 kg/hour and a Composite Desirability value of 0.983. These results indicate that proper arrangement of machine components can increase the efficiency of post-harvest chili processing.